A predatory activity of Oecophylla smaragdina (Hymenoptera : Formicidae) on citrus pests - Nur Adila Kamaruddin; Nabilah Zolkepli; Nur Syahida Wadhihah Kamarudin; Norasmah Basari (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Oecophylla smaragdina (weaver ant) is an aggressive predator that is common throughout plantation areas. However, the predatory activity of this ant species on crop pests is not clearly analyzed and reported. Hence, this study was conducted to determine the predatory activity of the weaver ant on citrus plant (Calamansi) at Taman Pertanian Negeri Sekayu Terengganu, Malaysia was done. The weaver ant was found preyed on various species of insect pests on citrus plant during foraging. Our result showed that 90% of the prey items were pests to the Calamansi tree and only 10% are non-pest insects. The highest number of insect pests is under the order of Hemiptera, which dominates about 38% of pest insects, and 52% of the total insect pests are considered as the major pests to citrus plants. In this study, the potential of using O. smaragdina as a biocontrol agent on various crop pests is highlighted.